Temozolamide - Najman, Henry (2002)
Temozolamide (TMZ) is a new class of alkylating agents deriving from imidazotetrazine. TMZ is a substance of low molecular weight, and 100% of it is absorbed via the oral route; and it is eliminated by the body about 8 hours after intake. Due to the swift elimination ratio and to its action, TMZ presents decreased risk of being toxic to the marrow bone. On the other hand, being a lipophylic substance, TMZ crosses the blood-brain barrier and may reach brain tumors. This drug is active againt some solid tumors, and it has been studied for the treatment of highgrade gliomas, including anaplastic astrocytoma (AA), multiform glioblastoma (GBM), low-grade gliomas, and metastatic malignant melanoma (MM). This bibliography review made evident the lack of scientific grounds to allow TMZ to be a standard treatment for brain tumors or metastatic malignant melanoma.